Forens(om)ic medicine: omics in forensic medicine - Goel, Rajeev; Kumar, Deepak; Arora, Vijay (International Journal of Research in Medical Sciences, 2022)
The branch of science informally known as ‘omics’ are various branches in biology whose names end in the suffix omics such as proteomics, metabolomics, genomics, transcriptomics. The studies regarding the role of omics in various branches of medical field have become an upcoming area and its rising trend has been observed in the last decade. Omics has very recently emerged as an uprising field in forensic medicine also which is already known for its great participation with other branches like forensic toxicology, biochemistry, psychiatry, genetics. The use of state- of-the-art omics technologies has been explored in forensic medicine and sciences in establishing post mortem interval, drugs of abuse, intoxication and cause of death. The various forensic studies presently are aiming omics for future prospective. An elementary attempt has been made in this review article to briefly present the role and advantages of omics in forensic medicine. We, hereby, propose to call it forensomic medicine, to draw attention of the forensic professionals to this novel branch of science in order to encourage new studies to be used in medico legal applications.